2015
DOI: 10.1016/j.ygcen.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Plasma FGF21 concentrations, adipose fibroblast growth factor receptor-1 and β-klotho expression decrease with fasting in northern elephant seals

Abstract: Fibroblast growth factor (FGF)-21 is secreted from the liver, pancreas, and adipose in response to prolonged fasting/starvation to facilitate lipid and glucose metabolism. Northern elephant seals naturally fast for several months, maintaining a relatively elevated metabolic rate to satisfy their energetic requirements. Thus, to better understand the impact of prolonged food deprivation on FGF21-associated changes, we analyzed the expression of FGF21, FGF receptor-1 (FGFR1), β-klotho (KLB; a co-activator of FGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
2
3
0
Order By: Relevance
“…Besides, gen analysis suggested that FGFR1 may be a regulator of adipogenesis by increasing fat cell numbers [27]. Moreover, our results confirmed the former hypothesis that the expression of FGFR1 was mediated by FGF21 circulating levels [28]. This research may provide an alternative to the problem of metformin therapy.…”
Section: Discussionsupporting
confidence: 84%
“…Besides, gen analysis suggested that FGFR1 may be a regulator of adipogenesis by increasing fat cell numbers [27]. Moreover, our results confirmed the former hypothesis that the expression of FGFR1 was mediated by FGF21 circulating levels [28]. This research may provide an alternative to the problem of metformin therapy.…”
Section: Discussionsupporting
confidence: 84%
“…To determine whether the elevation in total adiponectin in dolphins on a C17:0-rich diet was preceded by an increase in FGF21, we utilized a commercial ELISA previously used to measure serum FGF21 in cattle ( 29 , 30 ). The serum FGF21 concentrations were highly variable among this study’s dolphin population (129–1599 pg/ml), but was within similar ranges reported for humans 21–5300 pg/ml ( 31 ), pregnant cows 15–1600 pg/ml ( 29 ), pigs 225–325 pg/ml ( 32 ), northern elephant seals ~100–500 pg/ml ( 33 ), and rhesus monkeys 10–325 pg/ml ( 34 ). Even though we observed no significant difference between FGF21 levels over time, FGF21 was highly correlated with the abundance of total adiponectin (Table 1 ).…”
Section: Discussionsupporting
confidence: 76%
“…For instance, MIR17HG , KL , and BCL2L11 have been shown involved in cell-survival, apoptosis, and cellular aging, respectively 22 - 24 . Genetic variants near KL have also been shown associated with fasting glucose levels as well 25 . TMEM18 is involved in cellular migration; HLA-DR5 and CMIP play crucial roles in immune mediated responses and have been implicated in various immunological disorders 26 , 27 .…”
Section: Discussionmentioning
confidence: 99%